Detection of Aichi virus genotype B in two lines of wastewater treatment processes. (August 2017) - Ibrahim, Chourouk; Hammami, Salah; Mejri, Selma; Mehri, Ines; Pothier, Pierre; Hassen, Abdennaceur
Abstract: Enteric viruses are released in important quantities into the environment where they can persist for a very long time. At very low doses, they can cause human gastroenteritis, and are responsible for a substantial number of waterborne diseases. The aims of this study were multiple: firstly, to study the circulation of Aichi viruses ( AiV ) in wastewater sampled at the scale of a pilot wastewater treatment plant; secondly, to evaluate the performance of two wastewater treatment procedures, as natural oxidizing lagoons and rotating Biodisks, concerning the AiV removal; and finally, to determine the different type of AiV genotype found during this study. Hence, the pilot wastewater treatment plant is principally irrigated by the wastewater of three neighbouring clinics. Wastewater samples were collected during 2011 from the two lines of biological treatment procedures. AiV detection in wastewater were achieved using the Reverse Transcription Polymerase Chain Reaction (RT-PCR) technique, and the identification of AiV genotype was realized by the direct sequencing of PCR products. The result revealed that AiV strains were identified in 50% (n = 51) of the wastewater samples. A significant increase of the AiV detection frequency was registered from upstream to downstream of the five ponds constituting the natural oxidizing lagoon process, and at the exit of the rotating Biodisks procedure. All detected AiV strains showed the highest nucleotide sequence identity to genotype B that has been recently observed in patients in Asia. This finding represented the first Tunisian survey that revealed and mentioned the first detection of AiV genotype B in sewage and by the same argued for a noticeable resistance or survival of this type of virus in the two lines of treatment considered. Graphical abstract: Image 1 Highlights: The increase of detection rate of AiV (50%) in wastewater in Tunisia. The first detection of AiV genotype B in sewage in Tunisia. The high resistance of AiV to two biological treatment procedures. A Clear difference of the monthly distribution of AiV during the year of study.